Kompensasi, Tingkat Pendidikan, Penempatan Kerja, Kesehatan Kerja, dan Keselamatan Kerja terhadap Kinerja Karyawan - Yunus Manao; Jholant Bringg Luck Amelia Br Sinaga; Antoni Benyamin Sitorus; Yusuf Togatorop (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of the effect of compensation, education level, job placement, occupational health, and work safety on employee performance on employee performance at PT. Hutama Infrastructure Works. This research method is descriptive quantitative. In this study the population used at PT. Hutama Karya Infrastructure as many as 130 employees and on purpose sampling using certain criteria so that 100 samples were obtained. Data analysis using multiple linear regression. The results showed that the compensation variable had a tcount of 2.050, while the ttable variable had a value of 1.66, with a significant 0.043; b) the tcount value of the education level variable has a value of 2,421 and a ttable of 1.66, with a significance level of 0.017<0.05; c) the tcount value of the work placement variable has a value of 2.062, ttable 1.66, and a significance level of 0.042<0.05; d) the t-count value of the work safety variable has an average of 2,565, with a t-table of 1.66, and a value level of 0.012 <0.05.; e) the tcount value of the occupational health variable has a value of 2.756, a ttable of 1.66, and a significant value of 0.007<0.05. In conclusion, compensation variables, education level, job placement, occupational health, and work safety have a positive and significant effect partially on the performance of employees of PT. Hutama Infrastructure Works. Compensation variables, education level, job placement, occupational health, and work safety have a significant effect simultaneously on employee performance on Employee Performance at PT. Hutama Infrastructure Works. Keywords: Occupational Health, Occupational Safety, Employee Performance, Compensation, Work Placement, Education Level